Chronic cheek ulcer caused by odontogenic cutaneous sinus tract. (June 2015) - Sato, Tomoya; Ichioka, Shigeru
Abstract: Cutaneous sinus tracts in the cheek region are caused by infection in the periapical area of the tooth. The diagnosis is challenging unless we consider a dental origin because such tracts occur uncommonly and mimic other common disorders. Additionally, affected patients often have no symptoms and they are usually unaware of the underlying dental condition. We experienced a case involving delayed diagnosis of an odontogenic cutaneous sinus tract. We herein report this case to illustrate a few key factors for early diagnosis. An 83-year-old man presented with a 4-year history of a chronic ulcerated wound on his right cheek. A probe was introduced from the wound to the upper alveolar bone. Computed tomography revealed a radiolucent area in the periapical region. We examined the patient's tooth, and purulent drainage from the gingival sulcus was identified. The patient was diagnosed with an odontogenic cutaneous sinus tract. We referred the patient to a dentist, who extracted the problematic tooth. The chronic ulcer and sinus healed 3 weeks after the tooth extraction. Odontogenic cutaneous sinus tracts are often misdiagnosed, and they lead to facial wounds and scarring. Therefore, we must be aware of the possibility of this condition. A dental origin must be considered for chronic ulcers involving the cheek, chin and submental areas. The clinical course of this patient suggests two important clinical issues for prompt diagnosis. First, physical examination, including palpation and probing, are helpful for exploration of sinus tracts. Second, computed tomography is useful to detect the sinus tract and affected teeth. Computed tomography provides radiographic evidence of the relationship between the tooth and cutaneous region, and it may be superior to radiography.